From triple to quadruple bottom line: embedding culture in sustainable development - Govinnage, S. (Sri Lanka Institute of Information Technology(SLIIT): Malabe, 2025)
The widely acclaimed Triple Bottom Line (TBL) framework Economy, Society, and Environment has shaped global sustainability discourse for nearly three decades. However, despite its vast influence, a structural limitation persists: TBL does not explicitly account for Culture, the epistemic, ethical, and community anchoring dimension through which societies interpret sustainability, negotiate values, and organise collective life. A growing body of literature across anthropology, Indigenous studies, and sustainability discourses notes this omission but does not provide a consolidated conceptual model that integrates Culture into mainstream sustainability frameworks. This paper addresses that gap by demonstrating why Culture constitutes the missing analytic and operational foundation within existing sustainability theories and practices. Drawing on peer-reviewed cross-cultural research, structured literature analysis, and qualitative reflections, the paper shows how Culture shapes ethics, decision-making, innovation, community resilience, and inter generational responsibilities. Indigenous Australian knowledge systems developed through 60,000 years of relational stewardship illustrate how cultural traditions encode sustainability principles that modern governance often sidelines or misinterprets. The paper proposes a Quadruple Bottom Line (QBL) model encompassing Economy, Society, Environment, and Culture as a robust, layered framework. By positioning Culture at the normative centre of sustainability thinking, the QBL framework ensures that progress remains ethical, human-centred, and grounded in place-based knowledge systems, instilling a sense of reassurance and confidence in its applicability.
Keywords: Australia; Culture; Ethics; Governance; Indigenous Knowledge; Quadruple Bottom Line (QBL); Sri Lanka; Sustainability; Triple Bottom Line (TBL)